EVALUASI KINERJA KERETA API PANGRANGO BOGOR-SUKABUMI (Universitas Esa Unggul, 2016)
This study discusses the performance of Railway Pangrango Bogor-Sukabumi, whether it is optimal or not. Tujan from this research is to know the condition of Kang Pangrango at the moment, to know the load factor and performance of Kang Pangrango at the moment and to know the public response to the condition and performance of Kang Pangrango. The theory used in this research are city planning theory and transportation planning and transportation basic concept. While the main base is the Minister of Transportation No.9 Year 2011 on Minimum Service Standards For Railway People Transportation. The research method used is descriptive quantitative with data collection techniques through literature study, observation, questionnaire distribution and interview with Pangranngo rail passengers. The results showed that Pangrango KA condition has met the minimum service standards and used as the main mode of transportation for the community to avoid congestion that occurs on Sukabumi-Bogor or vice versa. But the performance of Kang Pangrango is not optimal because some people still object to the tariff set by the PT. KAI, so there are still people who do not want to switch using Kang Pangrango. Therefore, it should be given a solution to overcome the existing problems for the performance of Pangrango train become more optimal. Â Keywords: performance evaluation, railway, minimum inter-city train service standard, railway performance